A clinical trial of the effect of a mouth-rinse prepared with Lippia sidoides Cham essential oil in dogs with mild gingival disease - Girao, VCC; Nunes-Pinheiro, DCS; Morais, S. M.; Sequeira, Julio Lopes [UNESP]; Gioso, M. A. (Elsevier B.V., 2003)
We evaluated the effect of a mouth-rinse prepared using Lippia sidoides essential oil (EO) in dogs with marginal gingivitis. German Shepherd dogs were distributed in two groups: control (control mouth-rinse) and EO (EO mouth-rinse). Both mouth-rinses were applied on the dogs' teeth every 2 days for 2 weeks. At day 0 and day 15, the scores for plaque-bacteria (P), calculus (C), gingivitis (G) and the inflammatory infiltrate (INF) were evaluated blindly. The results were analyzed by the Wilcoxon signed-rank and Mann-Whitney tests (P less than or equal to 0.05). P, C, G, and INF did not show any alteration in the control group, while in the EO group there were significant reductions in these scores. (C) 2003 Elsevier B.V. B.V. All rights reserved.
Keywords: inflammation; gingival tissue; dental scores; essential oil; Lippia sidoides; mouth-rinse